Figure 2 in On the three poorly known species of Dictyna Sundevall, 1833 (Araneae: Dictynidae) described from Armenia and Siberia - Marusik, Yuri M. (Zenodo, 2022)
Figure 2. Males of Dictyna arundinacea from the type locality of D. ignobilis (a–d, g–h) and from Yakutia (e–f). (a) male palp, prolateral view; (b, e) male palp, ventral view; (c, f) male palp, retrolateral view; (d, g–h) male, dorsal, lateral, and frontal views. Scale bars = 0.2 mm unless otherwise indicated. Published as part of Marusik, Yuri M., 2022, On the three poorly known species of Dictyna Sundevall, 1833 (Araneae: Dictynidae) described from Armenia and Siberia, pp. 415-422 in Journal of Natural History 56 (5-8) on page 418, DOI:10.1080/00222933.2022.2073479, http://zenodo.org/record/6758509